Regional Income Disparity In Malaysia: Is Sabah Converging, Catching-Up With Or Falling Behind Other States In Malaysia? - Muzafar, Shah Habibullah; Dayang Affizzah, Awang Marikan; Lim, Kian-Ping (UMS, 2009)
Whether poor economies tend to converge towards rich ones or else to diverge over time is an issue that has attracted the attention of policymakers and academics alike for some decades. Economic convergence or divergence is a topic of considerable interest and debate, not only for validating or otherwise the two leading and competing growth models (the neoclassical and the endogenous growth approaches) but also for its policy-oriented implications. In Malaysia, the issue of economic convergence is also much debated. Despite the various Malaysia Plans for the past three decades, regional disparity between states remains. Thus, the objective of the present paper is to address the question whether the state of Sabah has been converging, catching-up or falling behind the other states in Malaysia. Using annual data for the period 1965 to 2003, our univariate unit root test result suggest that the state of Sabah has been catching-up with other states except with the state of Terengganu. In this respect, the local government has an important role to play in enhancing growth by providing stable economic environment for investment and other productive economic activities. This will ensure convergence can take place in the future.